Diurnal behaviour and utilization of shade in Masai giraffes (Giraffa camelopardalis tippelskirchi) - Adolfsson, Ulrika (2009)
Observations were carried out in the Masai Mara National Reserve in southwestern Kenya, which is the northern part of the Mara-Serengeti ecosystem in Kenya and Tanzania. Activity and behaviour of Masai giraffes (Giraffa camelopardalis tippelskirchi) was recorded with one-minute intervals for continuous periods of approximately twelve hours per day for two weeks in February and March 2007. The total observation time was 200 hours in females, 116 hours in males and 99 hours in offspring. The aim of the study was to investigate diurnal behaviour of the Masai giraffe and in particular their use of shade.